a arca totok kerot: CREATION OF THE ARCA TOTOK KEROT BATIK MOTIFS APPLIED TO EVENING GOWN - Muhammad Arif Jati Purnomo; Sulistiana Etika (Indonesian Institute of the Arts Surakarta, 2025)
Abstract The final assignment for this work is entitled